Pengelolaan Sampah Rumah Tangga Dalam Upaya Membangun Kesadaran Warga Pentingnya Mengurangi Produksi Sampah - Joleha Joleha; Elvi Yenie; Imam Suprayogi; Bochari Bochari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The habit of littering is carried out in almost all circles of society, not only the poor, even those with higher education do it. Organic waste and plastic waste are the largest waste generated by households. Processing organic waste into compost and utilizing plastic waste into ecobricks are service activities that have been carried out at Putri Tujuh II Housing Estate, Pekanbaru. This service activity aims to provide understanding and application to residents in managing household waste, so it is hoped that there will be awareness of the importance of waste processing in reducing waste generation in Final Disposal Sites (TPA). The method used is socialization, field practice which is continuously accompanied by the implementing team until the end of the service period. The result of this activity is an increase in public knowledge about processing waste into compost and ecobricks that can be used at home, but there is a decrease in the level of awareness at the end of the activity. This is because residents are no longer assisted in carrying out waste processing activities, so it can be concluded that continuous team assistance is needed until there is a commercial container to accommodate the results of waste processing carried out by residents